Phenylalanine promotes alveolar macrophage pyroptosis via the activation of CaSR in ARDS - Tang, Yiding; Yu, Yue; Li, Ranran; Tao, Zheying; Zhang, Li; Wang, Xiaoli; Qi, Xiaoling; Li, Yinjiaozhi; Meng, Tianjiao; Qu, Hongping; Zhou, Mi; Xu, Jing; et al. (Frontiers in Immunology, 2023)
Acute respiratory distress syndrome (ARDS) is associated with high mortality rates in patients admitted to the intensive care unit (ICU) patients with overwhelming inflammation considered to be an internal cause. The authors’ previous study indicated a potential correlation between phenylalanine levels and lung injury. Phenylalanine induces inflammation by enhancing the innate immune response and the release of pro-inflammatory cytokines. Alveolar macrophages (AMs) can respond to stimuli via synthesis and release of inflammatory mediators through pyroptosis, one form of programmed cell death acting through the nucleotide-binging oligomerization domain-like receptors protein 3 (NLRP3) signaling pathway, resulting in the cleavage of caspase-1 and gasdermin D (GSDMD) and the release of interleukin (IL) -1β and IL-18, aggravating lung inflammation and injury in ARDS. In this study, phenylalanine promoted pyroptosis of AMs, which exacerbated lung inflammation and ARDS lethality in mice. Furthermore, phenylalanine initiated the NLRP3 pathway by activating the calcium-sensing receptor (CaSR). These findings uncovered a critical mechanism of action of phenylalanine in the context of ARDS and may be a new treatment target for ARDS.